Final safety and efficacy results from the CPX-351 early access program for older patients with high-risk or secondary acute myeloid leukemia. Issue 5 (15th April 2020) - Roboz, Gail J.; Larson, Melissa L.; Rubenstein, S. Eric; Solomon, Scott R.; Schiller, Gary J.; An, Qi; Chiarella, Michael; Louie, Arthur C.; Lin, Tara L.
Abstract: CPX-351, a dual-drug liposomal encapsulation of cytarabine and daunorubicin at a synergistic 5:1 molar drug ratio, achieved superior efficacy compared with conventional chemotherapy in older adults with newly diagnosed, high-risk/secondary acute myeloid leukemia (AML) in phase 2 and 3 studies. Prior to CPX-351 commercialization, an expanded access program (EAP) provided CPX-351 access for this population in the United States. In this phase 4, single-arm, open-label study (NCT02533115), 52 patients were treated with CPX-351 for 1–2 induction cycles and ≤4 consolidation cycles. The primary endpoint was safety. The most common serious adverse events were febrile neutropenia (19%), pneumonia (10%), and infection (8%). The 30- and 60-d mortality rates were 0% and 6%, respectively. Remission was achieved by 44% of patients; 90% of patients were alive at study completion. Overall, these results support outcomes from prior studies and the use of CPX-351 in older adults with newly diagnosed, high-risk/secondary AML.